Snakes of campo Grande municipality, Mato Grosso Do Sul state, central Brazil - Carvalho, Priscila Santos [UNESP]; da Silva, Leandro Alves; Ferreira, Vanda Lúcia; de Souza, Franco Leandro; Santana, Diego José (My University, 2018)
The Cerrado biome harbours one of the highest levels of squamate species richness globally. In the past few years, several new localities have been sampled, providing important data regarding snake diversity within this biome. Few reptile and/or snake inventories have been performed in the state of Mato Grosso do Sul, Brazil, and none have been carried out in the municipality of Campo Grande, the capital of this state. In this paper, we present the first list of snake species in the municipality of Campo Grande based on specimens housed in the Zoological Collection of the Universidade Federal de Mato Grosso do Sul. We recorded 38 species distributed in the families Dipsadidae (21), Colubridae (6), Viperidae (5), Elapidae (2); Anomalepididae, Boidae, Leptotyphlopidae and Typhlopidae (1 species each). The snake fauna of Campo Grande is characterized by species typical of open habitats, some of which are Cerrado endemics (e.g. Trilepida koppesi, Chironius flavolineatus, Chironius quadricarinatus, Simophis rhinostoma, Erythrolamprus frenatus, Phalotris matogrossensis, Bothrops moojeni and Bothrops pauloensis). Despite the number of species found, our accumulation curve shows that the richness in the municipality is higher, and more sampling efforts are needed.
Keywords: Cerrado; Hotspot; Inventory; Open formations; Savannah; Serpentes; Zoological collection